2002
DOI: 10.1152/japplphysiol.00732.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of confinement (110 and 240 days) on neuroendocrine stress response and changes of immune cells in men

Abstract: The aim of the study was to evaluate the effects of long-term confinement on stress-permissive neuroendocrine and immune responses in humans. Two groups of four male subjects were confined 240 days (group 240) or 110 days (group 110) in two space modules of 100 or 200 m3, respectively. During confinement, none of the volunteers developed psychic stress as could be examined and verified by a current stress test. However, in group 240 but not in group 110, the diurnal rhythm of cortisol secretion was slightly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…The lack of effect of confinement on IgM mRNA levels is not surprising, because the density of embryos or larvae per milliliter of water in miniaquariums was similar to the density used in our animal facility to rear them under classic conditions. Moreover, a previous study demonstrated that after 110 or 240 d of confinement, the numbers of B and T cells in human peripheral blood were unaffected (42).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of effect of confinement on IgM mRNA levels is not surprising, because the density of embryos or larvae per milliliter of water in miniaquariums was similar to the density used in our animal facility to rear them under classic conditions. Moreover, a previous study demonstrated that after 110 or 240 d of confinement, the numbers of B and T cells in human peripheral blood were unaffected (42).…”
Section: Discussionmentioning
confidence: 99%
“…As proof of existing stress and stressors, we used cortisol measurements in this study. Cortisol has also been used in previous isolation studies, which described a connection between cortisol levels and isolation related stressors [21]. As anticipated, longterm isolation had a significant effect on cortisol levels.…”
Section: Cortisolmentioning
confidence: 94%
“…This sympathoadrenergic stimulation reflects a stressful adaptation back to normal life. Chouker et al (2002) Fig. 3A, B Heart rate in the morning (open squares) and in the evening (black squares) before, during and after the 240-day isolation (A), and during the 110-day isolation (B).…”
Section: Discussionmentioning
confidence: 99%